2021
DOI: 10.1371/journal.pntd.0009523
|View full text |Cite
|
Sign up to set email alerts
|

Improving timeliness in the neglected tropical diseases preventive chemotherapy donation supply chain through information sharing: A retrospective empirical analysis

Abstract: Background Billions of doses of medicines are donated for mass drug administrations in support of the World Health Organization’s “Roadmap to Implementation,” which aims to control, eliminate, and eradicate Neglected Tropical Diseases (NTDs). The supply chain to deliver these medicines is complex, with fragmented data systems and limited visibility on performance. This study empirically evaluates the impact of an online supply chain performance measurement system, “NTDeliver,” providing understanding of the va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…They found that information sharing is positively associated with the timeliness of several key stages in the NTD supply chain. Additionally, information sharing and coordination appear to be more impactful when information is released publicly and especially by country programme staff instead of international partners (Kasparis et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that information sharing is positively associated with the timeliness of several key stages in the NTD supply chain. Additionally, information sharing and coordination appear to be more impactful when information is released publicly and especially by country programme staff instead of international partners (Kasparis et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…If they are to perform well while maintaining cost-effectiveness, supply chains need information about stock, consumption, shipments and other such variables almost in real time (Kasparis et al , 2021 ). Privett and Gonsalvez ( 2014 ) outline how communication worsens and shipment visibility deteriorates as products move further down in-country supply chains, leaving those at the lower level of the health system with little information as to when supplies will arrive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avelar-Sosa et al (2019) define SC performance as the capacity of organisations to understand the needs of their customers and fulfil customer needs with sufficient inventory levels through product availability and on-time deliveries. Besides the use of online measurements to improve information sharing and time to order and deliver medicines (Kasparis et al , 2021), the use of PM, information and technology and other management practices is crucial to MA in government hospitals (Dixit et al , 2019). The use of digital technology platforms for PM reduces medicines stockout by tracking and enabling decision-making through enhanced information flows and reduced delays in order fulfilment (Wang et al , 2022).…”
Section: Literature Review On Medicine Stockout In Public Health-care...mentioning
confidence: 99%